(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To design the profile of active elderly women with urinary incontinence (UI) participating in a physical activity program according to sociodemographic characteristics, health conditions, life habits and conditions associated with urinary loss. Methods: A quantitative, cross-sectional, non-probabilistic study of 59 active elderly women. The elderly woman whose score was ≥ 3 according to the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) was considered incontinent. A descriptive analysis was performed by calculating the absolute and relative frequencies. Results: Predominant age between 70 and 79 years(44.1%), widows (32.2%), white (59.3%), complete high school (40.6%) and living alone (52.5%) . The largest proportion never smoked (64.4%) or drank (47.5%), it did not fall in the last year (64.4%), hypertensive (55.9%), had between one and three births (71.2%), were overweight (42.4%) and it did not use an intimate protector (67.8%). Urgency UI was more frequent (50.9%), small amount losses (54.3%), frequency ≤ 1 time per week (42.6%), complaint of nocturia (81.4%) and time of UI between 1 and 4 years (64.4%). Conclusion: The study made it possible to design the profile of active elderly women with UI, which in this study resemble those found in the literature. It is important to emphasize the importance of multidisciplinary work in the search for preventive actions and specialized treatments, aiming to maintain and/or improve the quality of life of incontinent elderly.